Knowledge management between the experiences of practitioners and the judgment of distinguished leaders | إدارة المعرفة بين خبرات الممارسين وحكم القادة المرموقين - Ferhat | فرحات , Hashim | هاشم; Al Migren | المقرن, Abd Allah | عبد الله (King Fahad National Library | مكتبة الملك فهد الوطنية, 2023)
This work is the book Knowledge Management Matters: Words of wisdom from leading practitioners, published in 2018, co-authored by eleven researchers and experts in the field of knowledge management, and edited by: John Girard and Joann Girard. It was issued by one of the publishing houses famous for publishing practical works in the social sciences, which is Sagology. It did well when it made the entire book available for free on its website for anyone who wanted to read it. We have seen it published. This book, in its Arabic version - God willing - is entitled “Issues in Knowledge Management: Advice from Distinguished Practitioners.” | هذا العمل هو كتاب knowledge Management Matters: Words of wisdom from leading practitioners المنشور في عام 2018 والذي اشترك في تأليفه أحد عشر باحثا وخبيرا في مجال إدارة المعرفة، وحرره كل من: John Girard و Joann Girard وقد صدر عن إحدى دور النشر الشهيرة بنشر الأعمال العملية في العلوم الًاجتماعية، وهي Sagology وقد أحسنَت صنعا عندما أتاحت الكتاب كاملا مجانا عبر موقعها لمن يريد الًاطلاع عليه وقد رأينا أن يصدر هذا الكتاب في نسخته العربية -إن شاء الله- بعنوان «مسائل في إدارة المعرفة: نصائح من ممارسين مرموقين